2003
DOI: 10.1073/pnas.1031504100
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and structural role of the metal ion in dUTP pyrophosphatase

Abstract: The metal ion dependence of the catalytic activity of recombinant Escherichia coli dUTP pyrophosphatase (dUTPase), an essential enzyme preventing incorporation of uracil into DNA, has been investigated by steady-state kinetic, electron paramagnetic resonance, and electron nuclear double resonance methods. Values of k cat and kcat͞Km were 4.5 ؎ 0.1 s ؊1 and 0.49 ؎ 0.1 ؋ 10 6 M ؊1 ⅐s ؊1 in the absence of divalent metal ions, 14.7 ؎ 2.2 s ؊1 and 25.1 ؎ 7.4 ؋ 10 6 M ؊1 ⅐s ؊1 in the presence of Mg 2؉ or Mn 2؉ , and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 28 publications
(75 reference statements)
3
54
0
Order By: Relevance
“…Enzyme and nucleotide stock solutions were incubated with Chelex resin for 30 min, on ice, followed by pelleting the resin in an Eppendorf centrifuge. Chelex-treated components were shown to contain less than 0.1 ppm of magnesium or manganese using atomic absorption spectroscopy on a Varian Spectra AA220 spectrophotometer, as described previously (42).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme and nucleotide stock solutions were incubated with Chelex resin for 30 min, on ice, followed by pelleting the resin in an Eppendorf centrifuge. Chelex-treated components were shown to contain less than 0.1 ppm of magnesium or manganese using atomic absorption spectroscopy on a Varian Spectra AA220 spectrophotometer, as described previously (42).…”
Section: Methodsmentioning
confidence: 99%
“…Enzymes involved in the metabolism of nucleotide phosphates and DNA or RNA usually require divalent metal ions as co-factors. Recently, it was shown that dUTPase from E. coli also possesses a similar catalytic activity in the absence of Mg 2ϩ (42). It seems that dUTPases in general might have a less stringent need for Mg 2ϩ , which is therefore not an obligate but an enhancer co-factor of these enzymes.…”
Section: Cloning Expression and Purification Of D Melanogaster Dutmentioning
confidence: 99%
“…Protons released in the dUTPase reaction were detected by phenol red pH indicator in 1 mM HEPES pH 7.5 buffer also containing 150 mM KCl, 40 µM phenol red (Merck) and 5 mM MgCl 2 [34][35][36][37] …”
Section: Steady-state Colorimetric Dutpase Assaymentioning
confidence: 99%
“…1 An additional enzymatic activity, deamination of dCTP (deoxycytidine triphosphate) to dUTP, may also be carried out by bifunctional dUTPases in Archaea [2][3][4][5] and also in Mycobacterium tuberculosis (M. tuberculosis), which also has a monofunctional dUTPase. 6 The dUTPases comprise two structurally different classes: 7 first, the β sheet−type dUTPases, possessed by most organisms, employ a one-metal ion catalytic mechanism, [8][9] and usually form a homotrimer 10 or a monomer, 11 while the second class, the α helical-type dUTPases, possessed by kinetoplastids, 12 form dimers and employ a two-metal ion catalytic mechanism. [13][14] In β sheet-type trimeric dUTPases, each active site is constituted from motifs of all three protomers, which are all required to interact for achieving proper enzymatic activity.…”
Section: Introductionmentioning
confidence: 99%